MUST handbook 2002. (Styles and Classics Philippines, 1998)
Endorsed by the Department of Transportation and Communications as an official guide for motorists. It offers up-to-date practical information for travelers in Manila such as emergency hotlines, utility locations, latest road rules, and vehicle maintenance. It also contains Street Maps of Metro Manila and "Easy Maps" for frequently traveled destinations in the country. This edition features additional guides on keeping healthy while vacationing.